2006
DOI: 10.1128/jvi.01112-06
|View full text |Cite
|
Sign up to set email alerts
|

Growth Transformation of Human T Cells by Herpesvirus Saimiri Requires Multiple Tip-Lck Interaction Motifs

Abstract: Lymphoma induction and T-cell transformation by herpesvirus saimiri strain C488 depends on two viral oncoproteins, StpC and Tip. The major interaction partner of Tip is the protein tyrosine kinase Lck, a key regulator of T-cell activation. The Lck binding domain (LBD) of Tip comprises two interaction motifs, a proline-rich SH3 domain-binding sequence (SH3B) and a region with homology to the C terminus of Src family kinase domains (CSKH). In addition, biophysical binding analyses with purified Lck-SH2 domain su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Previous studies have shown that Tip interacts with multiple cellular proteins, such as Lck, STAT3, and p80, but only Lck has been shown to be required for transformation of HVS-infected T cells (4,9,22,31,39). To search for additional cellular Tip interaction partners that may contribute to in vitro T cell immortalization, the amino acid sequences of Tip proteins in various HVS subgroup C strains were analyzed, and a conserved glutamic acid-rich region at the amino terminus was discovered (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Tip interacts with multiple cellular proteins, such as Lck, STAT3, and p80, but only Lck has been shown to be required for transformation of HVS-infected T cells (4,9,22,31,39). To search for additional cellular Tip interaction partners that may contribute to in vitro T cell immortalization, the amino acid sequences of Tip proteins in various HVS subgroup C strains were analyzed, and a conserved glutamic acid-rich region at the amino terminus was discovered (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While Tip is not required for viral replication in culture, Tip expression is critical for T cell and Stp-C oncogene immortalization (13). Transformation of human T cells with recombinant HVS expressing a mutant Tip that is unable to bind Lck has shown that the Tip-Lck interaction is required for HVS-induced transformation of human T lymphocytes, while binding to STAT3 is not necessary (22,23). Tip also targets p80, a lysosomal protein that consists of an N-terminal WD repeat domain and a C-terminal coiled-coil domain.…”
mentioning
confidence: 99%
“…Moreover, some data indicate that phosphorylation within the activation loop in trans by other Src or non-Src family members can also occur (22). An additional mode of activation, which does not involve dephosphorylation of the C-terminal tyrosine, is conferred by high affinity interactions of the SH3 domain with its ligands, resulting in the competitive displacement of low affinity intramolecular interactions (19,(23)(24)(25). This results in an alignment of kinase domain residues critical for catalysis and enables productive binding of ATP and substrates (26).…”
mentioning
confidence: 99%
“…The function of StpC relies on a TRAF2 binding site that mediates NF-B activation (12,13). Tip (tyrosine kinase-interacting protein) was identified as a binding partner of the Src family kinase (SFK) Lck (14), and complex interactions with this kinase are required for viral transformation (15). The herpesvirus ateles oncogene tio substitutes for stpC and tip in the transformation of human T cells (16).…”
mentioning
confidence: 99%